PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF DENGAN PENDEKATAN SAINTIFIK PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU DI KELAS IV SD NEGERI 101969 TANJUNG PURBA - Lala Jelita Ananda; Nuraini Nuraini (Universitas Negeri Medan, 2019)
The purpose of the study was to determine the validity of the learning media, to find out the practicality of learning media developed on the theme of the beauty of diversity in my country. The type of research is development research (R & D) using a 4-D model consisting of four stages, namely Define, Design, Develop, and Disseminate. The subjects in this study were grade IV students of Tanjung Purba State Elementary School 101969 which numbered 23 students. The data collection technique in this study was to use the results of assessments on aspects of media feasibility and material feasibility, the results of teacher responses to the practicality of learning media and the results of student responses after product trials. Based on the results of the study obtained the results of the feasibility of learning media by media experts by 92%, the results of material feasibility by material experts I obtained a percentage of 83%, the results of material feasibility by material experts II obtained a percentage of 86% and the results of assessment of teacher responses to the practicality 92%. From learning activities and data analysis research conducted by researchers, it can be concluded that the Development of Learning Media Based on Interactive Multimedia with a Scientific Approach in the Theme of Beautiful Diversity in My Country is valid and practical for use in the teaching-learning process and in accordance with the characteristics of students in class IV Tanjung Purba State Elementary School 101969. Keywords: Learning Media, Interactive Multimedia, Scientific Approach.